Meat 4.0: principles and applications of industry 4.0 technologies in the meat industry - Echegaray, Noemí; Hassoun, Abdo; Jagtap, Sandeep; Tetteh-Caesar, Michelle; Kumar, Manoj; Tomasevic, Igor; Goksen, Gulden; Lorenzo, Jose Manuel (MDPI, 2022)
Meat 4.0 refers to the application the fourth industrial revolution (Industry 4.0) technologies in the meat sector. Industry 4.0 components, such as robotics, Internet of Things, Big Data, augmented reality, cybersecurity, and blockchain, have recently transformed many industrial and manufacturing sectors, including agri-food sectors, such as the meat industry. The need for digitalised and automated solutions throughout the whole food supply chain has increased remarkably during the COVID-19 pandemic. This review will introduce the concept of Meat 4.0, highlight its main enablers, and provide an updated overview of recent developments and applications of Industry 4.0 innovations and advanced techniques in digital transformation and process automation of the meat industry. A particular focus will be put on the role of Meat 4.0 enablers in meat processing, preservation and analyses of quality, safety and authenticity. Our literature review shows that Industry 4.0 has significant potential to improve the way meat is processed, preserved, and analysed, reduce food waste and loss, develop safe meat products of high quality, and prevent meat fraud. Despite the current challenges, growing literature shows that the meat sector can be highly automated using smart technologies, such as robots and smart sensors based on spectroscopy and imaging technology.
Keywords: authenticity; automation; digitalisation; fourth industrial revolution; meat; quality; robotics; safety; smart sensors; spectroscopy